Aplikasi Sistem Informasi Berbasis Web dalam Menunjang Komunikasi Publik - Annisa Nur Fatimah (Politeknosains, 2018)
Many events are hold especially in Solo, they run in social, education, religion, entertainment, etc. In this case, communication has a big role to inform and promote an event to public, and one of the successes of an event can be indicated by many visitors who participate in the event. Participant’s number of an event is influenced by the way and the strategy of promotion. It is important for event organizer to pay attention about it. This article is initiated by many events which are conducted in Solo however the information of the events are not well organized yet. Therefore this article discusses about a web system application as media solution to promote and inform the events to public. The website uses programming language including HTML and PHP with database MySQL. The research method includes analyzing system, designing system, and implementing system. The result of the research is a web system application of event that is used as a medium for promoting and informing solo events which can be accessed by people everywhere and every time.